The Correlation Between Electrodiagnostic Severity and Patient-Reported Disability Among Carpal Tunnel Syndrome Patients - Gülay Soykök; Emel Güler (Annals of Indian Academy of Neurology)
Background and Objectives: The use, easy applicability, and costs of accurate diagnostic tools and their utility for early diagnosis, efficient treatment, and follow-up are important. In this study, we aimed to evaluate how electrophysiologic data were reflected in the clinical data of the patients with carpal tunnel syndrome (CTS). Methods: This study included 102 patients with definitive CTS based on electroneuromyography. The Boston Carpal Tunnel Syndrome Questionnaire (BCTQ), the 36-item Short Form (SF-36) questionnaire of the general quality of life, the Visual Analog Scale (VAS), and the painDETECT (PD-Q) neuropathic pain questionnaire were administered by a clinical practitioner. Results: We found a moderate correlation between electrophysiologic measurements and VAS and a weak correlation between PD-Q scores. When we tested the mean scores of the SF-36 quality of life scale subscales for differences across the CTS groups, we found significant differences in the mean scores of the physical functioning, bodily pain, and social functioning subdomains by disease severity (P < 0.05 for each). While the BCTQ Symptom Severity Scale (BCTQ-SSS) was predictive of the early stages of CTS, we found that both BCTQ-SSS and BCTQ-Functional Status Scale scores increased in correlation with advanced stage CTS. Conclusion: In addition to the electrophysiological data, self-report measures may help to pursue a multidirectional approach in patient management by acting as a reference for the diagnosis, treatment, and monitoring of CTS. The correlation between objective data and time-saving, practical, subjective measurements can serve as markers to facilitate a diagnosis.